(untitled) (Journal of Medical & Health Sciences Review, 2025)
Background: Duodenal ulcer perforation is a life-threatening surgical emergency. With the advancement of minimally invasive techniques, laparoscopic repair has emerged as an alternative to conventional open surgery. However, comparative data on postoperative outcomes remains limited, especially in local contexts. Objective: To compare postoperative pain between laparoscopic and open surgical repair in patients with duodenal ulcer perforation. Methods: A randomized controlled trial was conducted at the Department of Surgery, Saidu Group of Teaching Hospital, Swat, over six months. Sixty patients with CT-confirmed duodenal ulcer perforation were enrolled and randomly assigned to laparoscopic (n=30) or open repair (n=30). Postoperative pain was assessed on postoperative day 3 using the Visual Analog Scale (VAS). Opioid consumption and time to return to normal activity were also recorded. Data were analyzed using IBM SPSS version 21. An independent sample t-test was used with a significance level of p<0.05. Results: The mean VAS pain score was significantly lower in the laparoscopic group (4.5 ± 0.7) than in the open group (6.7 ± 0.8; p<0.001). Opioid requirement in the first 24 hours was also significantly reduced in the laparoscopic group (40 ± 14 mg vs. 60 ± 12 mg; p=0.002). Return to normal activity was faster in the laparoscopic group (14 ± 2 days) compared to the open group (21 ± 4 days; p<0.001). Although operative time was longer in the laparoscopic group (140 ± 18 minutes vs. 110 ± 15 minutes), this did not affect clinical outcomes. Conclusion: Laparoscopic repair of duodenal ulcer perforation is associated with significantly lower postoperative pain, reduced analgesic needs, and faster recovery than open repair, despite a longer operative time. These findings support the broader adoption of laparoscopic techniques in suitable patients, with the caveat of a small sample size and need for further large-scale trials.